Rotary ultrasonic machining of CFRP: a comparison with twist drilling - Cong, W. L.; Pei, Zhijian J.; Feng, Q.; Deines, Timothy W.; Treadwell, C. (My University, 2012)
Drilling is involved in many applications of carbon fiber reinforced plastic (CFRP) composite. Twist drilling is widely used in industry. Rotary ultrasonic machining (RUM) has been successfully tested to drill holes in CFRP. However, there are no reports on comparisons between RUM and twist drilling of CFRP. This paper compares RUM and twist drilling of CFRP in six aspects (cutting force, torque, surface roughness, delamination, tool life, and material remove rate). Experimental results show that RUM is superior in almost all these aspects.
Keywords: Carbon fiber reinforced plastic composite; Cutting force; Rotary ultrasonic machining; Surface roughness; Tool wear; Twist drilling